From Paris to Jakarta: How Terror Attacks Drive Mobile Engagement - Mahzam, Remy (2016)
Thanks to mobile communication, the 14 January Jakarta attacks were documented by eye-witnesses through their mobile phone cameras and distributed over quick-sharing applications. This also brought the experience to a whole new level, with the spectre of terrorism making its way into the personal spaces of those on mobile connectivity.